Surface-enhanced raman scattering: metal nanostructures coated with langmuir-blodgett films - Alessio, Priscila [UNESP]; Constantino, Carlos J. L. [UNESP]; Aroca, Ricardo F.; Oliveira, Osvaldo N. (Soc Chilena Quimica, 2010)
This review deals with surface-enhancved Raman scattering (SERS) employing Langmuir-Blodgett (LB) films, which serve as model systems for developing theoretical and experimental studies to elucidate the SERS effect. In addition, LB films have be used as integral parts of molecular architectures for SERS-active substrates. on the other hand, SERS and surface-enhaced resonant Raman scattering (SERRS) have allowed various properties of LB films to be investigated, especially those associated with molecular-level interactions. In the paper, emphasis is placed on single molecule detection (SMD), where the target molecule is diluted on an LB matrix of spectral silent material (low Raman cross section). The perspectives and challenges for combining SERS and LB films are also discussed.
Keywords: Surface-enhanced Raman scattering; plasmonics; Langmuir-Blodgett films; nanoparticles